A Comparison of Corrosion Behavior of Copper and Its Alloy in Pongamia pinnata Oil at Different Conditions. (3rd April 2013) - Parameswaran, Meenakshi H. N.; Anand, Anisha; Krishnamurthy, Shyamala R.
Abstract : Vegetable oils are promising substitutes for petrodiesel as they can be produced from numerous oil seed crops that can be cultivated anywhere and have high energy contents, exhibiting clean combustion behavior with zero CO2 emission and negligible SO2 generation. The impact of biofuel on the corrosion of various industrial metals is a challenge for using biofuel as automotive fuel. Fuel comes in contact with a wide variety of metallic materials under different temperatures, velocities, and loads thereby causing corrosion during storage and flow of fuel. Hence, the present investigation compares the corrosion rates of copper and brass in Pongamia pinnata oil (O100), 3% NaCl, and oil blend with NaCl (O99) obtained by static immersion test and using rotating cage. The corrosivity and conductivity of the test media are positively correlated. This study suggested that the corrosivity of copper is higher than brass in Pongamia pinnata oil (PO).